The Nexus Between Bitcoin and CO2 Emissions - Unal, Emre; Kose, Nezir (Wiley, 2025)
This research examined the connection between Bitcoin, the prominent and extensively mined cryptocurrency, and CO2 emissions using the SVAR model. Azerbaijan, Kazakhstan, and Russia, the three main countries in the Caspian Basin that are the centre of cryptocurrency mining, were examined in terms of their primary industries. The variance decomposition analysis indicated that the Bitcoin price had the most significant explanatory role in CO2 emissions released by Oil and Natural Gas industry in Azerbaijan. When it comes to the CO2 emissions that were emitted by the Petroleum Refining-Manufacture of Solid Fuels and Other Energy industry, as well as Manufacturing Industries and Construction, the Bitcoin price had the most important effect in Kazakhstan. There was a significant contribution made by Bitcoin to the CO2 emissions that were emitted by the Manufacturing Industries and Construction in Russia. The impulse response functions illustrated a strong association between Bitcoin and CO2 emissions. However, in contrast to existing research, this relationship was found to be negative. The increase in energy usage during Bitcoin price falls can be attributed to the need to compensate for losses, particularly in the mining process. To diminish this connection, the dependence of the cryptocurrency on fossil fuels must be minimised.
Keywords: Bitcoin; Caspian Basin countries; CO2 emissions; energy price; SVAR model